ANALYSIS OF PHYSICAL CONDITION QUALITY IN HIGH SCHOOL STUDENTS’ FUTSAL EXTRACURRICULAR ACTIVITIES - Kurniasandi, Iman; Imanudin, Iman; Umaran, Unun (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
This study aims to assess the physical fitness levels of futsal athletes participating in extracurricular programs at six high schools in Tangerang City. Using a quantitative research method with a survey and analysis approach, data were collected from 60 students aged 16 to 18 years through purposive and area sampling. Six physical fitness tests were conducted: Sit and Reach (flexibility), Vertical Jump, Triple Hop Jump, Hurdle Jump (power), Illinois Agility Test (speed and agility), and Beep Test (endurance). The average scores of the participants were compared to normative data for both general non-athlete adolescents and trained athletes. Results showed that while the futsal athletes outperformed the general adolescent population in most fitness components, their performance was significantly lower than that of elite athletes, particularly in endurance and lower limb power. The findings indicate a need for improved training programs that emphasize physical conditioning alongside technical and tactical skills. Plyometric exercises, agility drills, and cardiovascular training are recommended to enhance the athletes’ physical capacities. This research highlights the importance of balanced training in school sports programs and recommends that coaches incorporate comprehensive fitness training tailored to students’ individual needs. Overall, enhancing physical fitness is essential for maximizing the performance and success of young futsal athletes